Strain background interacts with chromosome 7 aneuploidy to determine commensal and virulence phenotypes in Candida albicans. - Abhishek Mishra; Norma V Solis; Siobhan M Dietz; Audra L Crouch; Scott G Filler; Matthew Z Anderson (PLoS Genetics)
The human fungal pathobiont Candida albicans displays extensive genomic plasticity, including large-scale chromosomal changes such as aneuploidy. Chromosome trisomy appears frequently in natural and laboratory strains of C. albicans. Trisomy of specific chromosomes has been linked to large phenotypic effects, such as increased murine gut colonization by strains trisomic for chromosome 7 (Chr7). However, studies of whole-chromosome aneuploidy are generally limited to the SC5314 genome reference strain, making it unclear whether the imparted phenotypes are conserved across C. albicans genetic backgrounds. Here, we report the presence of a Chr7 trisomy in the "commensal-like" oral candidiasis strain, 529L, and dissect the contribution of Chr7 trisomy to colonization and virulence in 529L and SC5314. These experiments show that strain background and homolog identity (i.e., AAB vs ABB) interact with Chr7 trisomy to alter commensal and virulence phenotypes in multiple host niches. In vitro filamentation was consistently reduced by Chr7 trisomy in SC5314, but this result was not consistent for 529L. Oral colonization of mice was increased by the presence of a Chr7 trisomy in 529L but not SC5314; conversely, virulence during systemic infection was reduced by Chr7 trisomy in SC5314 but not 529L. Strikingly, the AAB Chr7 trisomy in the SC5314 background rendered this strain avirulent in murine systemic infection. Increased dosage of NRG1 failed to reproduce most of the Chr7 trisomy phenotypes. Our results demonstrate that aneuploidy interacts with background genetic variation to produce complex phenotypic patterns that deviate from our current understanding in the genome reference strain.